Serum Magnesium Level among the Patients Admitted with Acute Stroke in a Tertiary care Hospital - Hossain, Md Firoj; Hasan, MN; Uddin, SM; Masum, AA; Basak, PM (TAJ: Journal of Teachers Association, 2018)
Magnesium deficiency was shown to trigger vasoconstriction and enhance vascular endothelial injury, thus promoting the development and progression of atherosclerosis. We hereby intended to investigate serum magnesium in the early stage of acute stroke and to evaluate the relationship between serum magnesium concentration and the development of neurological deficits. This is a descriptive type of cross sectional study was carried out in department of medicine, Comilla Medical College Hospital from June 2013 to December 2013. Fifty admitted acute stroke patients were randomly chosen for this study who fulfills inclusion criteria. The serum magnesium concentrations were measured by photometric colorimetric end point method on admission. Out of 50 acute stroke patients 30 (60%) were male and 20 (40%) were female. The mean age is 66.44 (SD ±14.8) years with male predominance. Most of the patients 30 (60%) belongs to above 60 years and 36 (72%) patients had hypomagnesaemia and 14 (28%) had normal serum magnesium level. Serum magnesium level more low in ischemic stroke (56%) . The mean serum magnesium level was 1.59 (SD ±0.37) mg/dl in all stroke patient and 1.47 (SD ±0.32) mg/dl in ischemic stroke patient was and was 1.83 (SD ±0.34) mg/dl in hemorrhagic stroke patients. Among 33 ischemic stroke patients mostly 17 (34%) patients had serum magnesium level between 1.0-1.4 mg/dl and in hemorrhagic stroke patients maximum 05 (10%) serum magnessium level was in between 1.5-1.8 mg/dl (P-value 0.0017 HS). In our study most of the patients with acute stroke were improved with marked residual disability were [19 (38.0%)], improved with minimal residual disability were [08 (16%)], improved without residual disability [04 (08%)] and death [03 (6%)] having hypomagnesaemia compared to the patients who have normal serum magnesium level with maximum improvement with minimal residual disability were [10 (20.0%)], improved without residual disability were [06 (12%)], improved with marked residual disability and death were [0 (0%)]. Gross clinical outcome disability of acute stroke patients was worse who had hypomagnesaemia (P-value 0.001 significant). Magnesium levels are significantly decreased in acute stroke; both in ischemic stroke patients as well as in patients of hemorrhagic. Patients with low serum magnesium level in acute stroke associated with worse clinical outcome. TAJ 2014; 27(1): 50-56